Cyber security - Avantika Yadav (Narosa, 2017)
CYBER SECURITY is a combination of technologies, processes and practices designed to protect networks, computers, programs and data from attack, damage or unauthorized access. In a computing context, security includes both cyber security and physical security. This book gives brief introduction about the cyber security basics and related terms such that a reader from non-computer background may also be able to understand. It covers the entire syllabus of cyber security subject, which is essential audit course for all the courses and all the branches irrespective of the specialization. This is a most practical and up-to-date reference for Cyber Security.